An empirical investigation on the role of Barakah in the Islamic theory of consumer choice - Munrokhim Misanam (Penerbit Universiti Kebangsaan Malaysia, 2009)
Conventional consumer theory biased toward western values. Eventhough there is a soaring claim of being free from any value, but the fact shows that the formulation of action resulted from western economic analysis biases strongly toward the core of western value, that is, individualistic value. However the value loaded in western theory of consumer choice does not match the Islamic teaching. In this paper a theoreticaI model implied by Islamic values which represents the behaviour of Moslem consumer in choosing goods among alternatives. From empirical evidence, the results show that awareness, consistency and neutrality come together and simultaneously, it is safe to say that awareness implies consistency. While consistency further implies neutrality. This means that the revelation-deduction-based prediction over the relationship between awareness, consistency and neutrality meets reality. This shows that Moslem consumers does aware of the existence and the extent of barakah in the product they are considering to buy. They also behave rationali'y in that they make a consistent buying decision based on their investigation. Finally, when seeing two goods with drfferent barakah content they willfind it easy to neglect the one with no barakah in it eventhough the price is lower: This further implies that the practice of lslamic theory of consumption does exist, and therefore, abort the accusition that blamic economics is merely normative.